Composite fiber filtering material

By combining polyphenylene sulfide, polytetrafluoroethylene and modified glass fiber to prepare composite fiber filter materials, the problem of existing fiber filter materials being prone to break in high temperature or strong oxidation environments is solved, and the multiple performance improvement of the material is achieved, meeting the needs of efficient filtration and environmental protection.

CN119588076AInactive Publication Date: 2025-03-11ANHUI UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411692286.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing fiber filter materials are prone to fracture under high temperature or strong oxidation environments, and the performance of a single material is insufficient, making it difficult to meet the needs of efficient filtration and environmental protection.

Method used

The composite fiber filter material is made of polyphenylene sulfide, polytetrafluoroethylene and modified glass fibers, and is prepared by mixing and melt spinning processes, combining lubricants to improve the mechanical properties and corrosion resistance of the material.

Benefits of technology

The excellent mechanical properties, heat resistance, flame retardant and corrosion resistance of composite fiber filter materials are achieved, and the oxidation resistance is enhanced, which meets the needs of efficient filtration and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005151270930000031
    Figure BDA0005151270930000031
  • Figure BDA0005151270930000032
    Figure BDA0005151270930000032
  • Figure BDA0005151270930000041
    Figure BDA0005151270930000041
Patent Text Reader

Abstract

The invention discloses a composite fiber filter material, and belongs to the technical field of filter materials. Comprising the following raw materials in parts by weight: 60-80 parts of polyphenylene sulfide resin, 15-25 parts of polytetrafluoroethylene, 7-21 parts of modified glass fibers and 3-7 parts of a lubricant. By compounding the polyphenylene sulfide, the polytetrafluoroethylene and the glass fiber, the excellent properties of the three materials are combined, the complementation of the properties is realized, and the material is endowed with excellent mechanical properties, heat resistance, flame retardance and corrosion resistance; besides, the glass fibers are modified, so that the performance of the glass fibers is fully played, and moreover, organic molecules grafted on the surfaces of the modified glass fibers can enhance the oxidation resistance of the material, and the performance is stable. In conclusion, the filter material prepared by the invention is excellent in mechanical property, heat resistance, flame retardance and corrosion resistance, also has stable and efficient oxidation resistance, and has important application value in the technical field of filter materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of filter materials, and in particular relates to a composite fiber filter material. Background Art

[0002] With the development of industry, coal burning has also increased. Coal-fired power generation emits 5 million tons of dust every year. This type of industrial dust occupies an important position in air pollution, and most of the dust is fine dust. Not only that, the flue gas also contains SO2, NO X Highly acidic gases such as HC, if discharged directly without being filtered, will cause serious environmental pollution.

[0003] Fiber filter materials are widely used in air filtration, especially in environments with high-temperature dusty exhaust gas emissions. They can intercept suspended particles and reduce environmental pollution. Common fiber filter materials include high-temperature filter materials such as PPS (polyphenylene sulfide), PTFE (polytetrafluoroethylene) and GF (glass fiber). Among them, polyphenylene sulfide is a polymer that forms a macromolecular rigid main chain by connecting sulfur atoms in the para position with benzene rings. It has excellent strength, rigidity and fatigue resistance at high temperatures, and has good heat resistance and corrosion resistance. However, the CS bond energy on the polyphenylene sulfide macromolecular chain is low, and it is easy to break and undergo oxidative cross-linking under high temperature or strong oxidizing environment conditions. Therefore, polyphenylene sulfide fiber has poor resistance to corrosive gases such as oxidants. Polytetrafluoroethylene is made by free radical polymerization of tetrafluoroethylene and has extremely strong high temperature resistance, chemical stability and non-flammability, but polytetrafluoroethylene has low strength and poor dimensional stability, and is difficult to use alone. Finally, glass fiber has high mechanical properties and heat resistance, but its acid resistance is poorer than that of PPS and PTFE. Therefore, combining the advantages of the three materials to prepare a composite fiber filter material can effectively solve the problem of insufficient performance of a single fiber and meet higher requirements in the field of filter material technology. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a composite fiber filter material.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A composite fiber filter material is prepared by the following steps:

[0007] The polyphenylene sulfide resin, polytetrafluoroethylene and modified glass fiber are dried in an oven at 80-100°C, added to a high-speed mixer with a lubricant for mixing, and then added to a twin-screw extruder for melt spinning to obtain a composite fiber filter material.

[0008] Furthermore, the raw materials are calculated in parts by weight as follows: 60-80 parts of polyphenylene sulfide resin, 15-25 parts of polytetrafluoroethylene, 7-21 parts of modified glass fiber, and 3-7 parts of lubricant.

[0009] Furthermore, the lubricant is one of paraffin and epoxidized soybean oil.

[0010] With polyphenylene sulfide as the main matrix, the filter material is endowed with excellent strength, high temperature resistance and corrosion resistance; the addition of polytetrafluoroethylene can further enhance the high temperature resistance and corrosion resistance of the filter material, and can also enhance the flame retardant properties of the filter material.

[0011] Furthermore, the modified glass fiber is prepared by the following steps:

[0012] S1. Soak the chopped glass fiber in acetone for 12 hours, wash with distilled water, dry in an oven, add to ethanol aqueous solution, add silane coupling agent KH-550, control the temperature to 85°C, keep warm for 5 hours, stir continuously during the reaction, filter, wash with anhydrous ethanol, and vacuum dry for 2 hours to obtain pre-modified glass fiber; the ratio of glass fiber, acetone, ethanol aqueous solution, and silane coupling agent KH-550 is 1g:100mL:100mL:7.2g;

[0013] The chopped glass fibers were pre-modified using silane coupling agent KH-550, and active amino groups were introduced on the surface of the chopped glass fibers to obtain pre-modified glass fibers.

[0014] S2, in a three-necked flask equipped with a reflux device, 2-methyl-6-tert-butylphenol and potassium hydroxide were mixed, nitrogen was introduced into the device, and under the protection of nitrogen, the reaction temperature was controlled to be 50°C, and the reaction was kept warm for 2 hours, and methyl acrylate was added dropwise. After the addition was complete, the temperature was raised to 140°C, and the reflux reaction was carried out for 4 hours. After the reaction was completed, the mixture was cooled to room temperature, toluene was added, and the pH was adjusted to 7 with hydrochloric acid solution (mass fraction 12%), and the aqueous phase and the organic phase were separated by standing, and the organic phase was taken to remove toluene by vacuum distillation. The temperature was continued to be raised, and the fraction between 190-210°C was collected as intermediate 1; the ratio of 2-methyl-6-tert-butylphenol, potassium hydroxide, and methyl acrylate was 16.4g:0.5g:9.5g;

[0015] Under the catalysis of potassium hydroxide, 2-methyl-6-tert-butylphenol reacts with methyl acrylate to obtain intermediate 1; the specific reaction process is as follows:

[0016]

[0017] S3, add intermediate 1, thiodiethanol, lithium diisopropylamide (catalyst, LAD) and N, N-dimethylformamide (DMF) to a three-necked flask equipped with a stirring device, stir and mix evenly, pass nitrogen to remove air, heat to 90°C, react for 8 hours, and after the reaction is completed, remove the solvent by reduced pressure distillation, and then purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate, the volume ratio of the two is 1:2), and remove the eluent by rotary evaporation to obtain intermediate 2; the ratio of the amount of intermediate 1, thiodiethanol, lithium diisopropylamide, and N, N-dimethylformamide is 24.9g:15.2g:0.4g:100mL;

[0018] Under the catalysis of lithium diisopropylamide, intermediate 1 undergoes an ester exchange reaction with thiodiethanol. By controlling the molar ratio of the two to be close to 1:1 and a slight excess of thiodiethanol, only one hydroxyl group on thiodiethanol participates in the reaction to obtain intermediate 2. The specific reaction process is as follows:

[0019]

[0020] S4. In a three-necked flask equipped with a stirring device, the intermediate 2, terephthalic acid and N,N-dimethylformamide were mixed and stirred evenly, and then dibutyltin oxide (catalyst) and dicyclohexylcarbodiimide (DCC, dehydrating agent) were added, and the reaction temperature was controlled to 85°C. The reaction was kept warm for 8 hours, and stirring was continued during the reaction. After the reaction was completed, the mixture was filtered, and part of the solvent was removed by rotary evaporation. Then, the mixture was purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 2:3), and the eluent was removed by rotary evaporation to obtain intermediate 3; the ratio of the amount of intermediate 2, terephthalic acid, N,N-dimethylformamide, dibutyltin oxide and dicyclohexylcarbodiimide was 34.0 g:21.7 g:150 mL:0.3 g:20.6 g;

[0021] Under the catalysis of dibutyltin oxide and dicyclohexylcarbodiimide, the hydroxyl group on the intermediate 2 and the carboxyl group on the terephthalic acid undergo esterification reaction. By controlling the molar ratio of the two to be close to 1:1 and the terephthalic acid to be slightly excessive, only one carboxyl group on the terephthalic acid participates in the reaction to obtain the intermediate 3. The specific reaction process is as follows:

[0022]

[0023] S5, ultrasonically disperse the pre-modified glass fiber in N,N-dimethylformamide for 30 minutes, add intermediate 3 and dicyclohexylcarbodiimide, mix and stir evenly, stir and react in a water bath at 55°C for 8 hours, stop heating after the reaction is completed, wait until the temperature drops to room temperature, filter, take the filter residue, wash it with anhydrous ethanol 3-4 times, and dry it to obtain modified glass fiber; the ratio of the amount of pre-modified glass fiber, N,N-dimethylformamide, intermediate 3, and dicyclohexylcarbodiimide is 1g:100mL:8.1g:7.4g;

[0024] Under the catalysis of dicyclohexylcarbodiimide, the amino group on the pre-modified glass fiber and the carboxyl group on the intermediate 3 molecule undergo amidation reaction to obtain modified glass fiber;

[0025] Chopped glass fiber is an excellent reinforcement material with good heat resistance and mechanical properties. By modifying the chopped glass fiber, that is, forming an organic layer on its surface, the interfacial compatibility between the chopped glass fiber and the polyphenylene sulfide matrix can be greatly improved, thereby promoting the uniform dispersion of the chopped glass fiber in the matrix, reducing the agglomeration phenomenon, and giving full play to the performance of the chopped glass fiber, and greatly improving the mechanical properties and heat resistance of the matrix; in addition, the modified glass fiber also contains thioester and semi-hindered phenol structures, wherein the thioester, as an auxiliary antioxidant, can synergize with hindered phenol and greatly enhance the antioxidant properties of the matrix. Moreover, compared with the traditional fully hindered phenol antioxidant, the semi-hindered phenol structure antioxidant has an ortho-substituent with an appropriate steric hindrance effect, which reduces the bond dissociation energy between the phenolic hydroxyl groups and increases the collision probability between the phenolic hydroxyl groups and the system free radicals, has a higher ability to scavenge free radicals, and has better thermal oxidation resistance; finally, the modified glass fiber also contains a benzene ring, which further enhances the compatibility with polyphenylene sulfide;

[0026] It should be noted that glass fiber is an inorganic material, and organic molecular chains are grafted onto its surface, making it difficult for them to seep out and migrate, thus ensuring the long-term stability of the performance of the modified glass fiber.

[0027] Beneficial effects of the present invention:

[0028] The filter material prepared by the present invention combines the excellent properties of the three materials by compounding polyphenylene sulfide, polytetrafluoroethylene and glass fiber, realizes the complementary properties, and gives the filter material excellent mechanical properties, heat resistance, flame retardant properties and corrosion resistance; in addition, by hydrophobic modification of glass fiber, the inorganic glass fiber has better compatibility with polyphenylene sulfide and polytetrafluoroethylene, which promotes the dispersion of glass fiber and makes the performance of glass fiber fully exerted. Moreover, the organic molecules grafted on the surface of modified glass fiber can play a synergistic role, greatly enhance the antioxidant properties of the filter material, and the performance is long-term and stable and not easy to fall off. In summary, the filter material prepared by the present invention has excellent mechanical properties, heat resistance, flame retardant properties and corrosion resistance, and also has stable and efficient antioxidant properties, and has important application value in the field of filter material technology. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Embodiment 1

[0031] Preparation of modified glass fiber:

[0032] S1. Soak 1g of chopped glass fiber in 100mL of acetone for 12h, wash with distilled water, dry in an oven, add to 100mL of ethanol aqueous solution, add 7.2g of silane coupling agent KH-550, control the temperature to 85°C, keep warm for 5h, stir continuously during the reaction, filter, wash with anhydrous ethanol, and vacuum dry for 2h to obtain pre-modified glass fiber;

[0033] S2, in a three-necked flask equipped with a reflux device, 16.4g of 2-methyl-6-tert-butylphenol and 0.5g of potassium hydroxide were mixed, nitrogen was introduced into the device, and under the protection of nitrogen, the reaction temperature was controlled to 50°C, and the reaction was kept warm for 2h, and 9.5g of methyl acrylate was added dropwise. After the addition was complete, the temperature was raised to 140°C, and the reflux reaction was carried out for 4h. After the reaction was completed, it was cooled to room temperature, toluene was added, and the pH was adjusted to 7 with hydrochloric acid solution (mass fraction 12%), and the aqueous phase and the organic phase were separated by standing, and the organic phase was taken to remove toluene by vacuum distillation. The temperature was continued to be raised, and the fraction between 190-210°C was collected as intermediate 1;

[0034] S3, in a three-necked flask equipped with a stirring device, add 24.9g of intermediate 1, 15.2g of thiodiethanol, 0.4g of lithium diisopropylamide and 100mL of N,N-dimethylformamide, stir and mix well, pass nitrogen to remove air, heat to 90°C, react for 8h, and after the reaction is completed, remove the solvent by vacuum distillation, and then purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate, the volume ratio of the two is 1:2), and remove the eluent by rotary evaporation to obtain intermediate 2;

[0035] S4, in a three-necked flask equipped with a stirring device, 34.0g of intermediate 2, 21.7g of terephthalic acid and 150mL of N,N-dimethylformamide were mixed and stirred evenly, and then 0.3g of dibutyltin oxide and 20.6g of dicyclohexylcarbodiimide were added, and the reaction temperature was controlled to 85°C, and the reaction was kept warm for 8h. Stirring was continued during the reaction. After the reaction was completed, the reaction was filtered, and part of the solvent was removed by rotary evaporation. Then, it was purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 2:3), and the eluent was removed by rotary evaporation to obtain intermediate 3;

[0036] S5. Ultrasonic disperse 1 g of pre-modified glass fiber in 100 mL of N,N-dimethylformamide for 30 min, add 8.1 g of intermediate 3 and 7.4 g of dicyclohexylcarbodiimide and mix well. Stir and react in a water bath at 55 °C for 8 h. After the reaction is completed, stop heating. After the temperature drops to room temperature, filter and take the filter residue. Wash it three times with anhydrous ethanol and dry it to obtain modified glass fiber.

[0037] Embodiment 2

[0038] Preparation of modified glass fiber:

[0039] S1. Soak 2 g of chopped glass fiber in 200 mL of acetone for 12 h, wash with distilled water, dry in an oven, add to 200 mL of ethanol aqueous solution, add 14.4 g of silane coupling agent KH-550, control the temperature to 85 ° C, keep warm for 5 h, stir continuously during the reaction, filter, wash with anhydrous ethanol, and vacuum dry for 2 h to obtain pre-modified glass fiber;

[0040] S2, in a three-necked flask equipped with a reflux device, 32.8g of 2-methyl-6-tert-butylphenol and 1.0g of potassium hydroxide were mixed, nitrogen was introduced into the device, and under the protection of nitrogen, the reaction temperature was controlled to 50°C, and the reaction was kept warm for 2h, and 19.0g of methyl acrylate was added dropwise. After the addition was complete, the temperature was raised to 140°C, and the reflux reaction was carried out for 4h. After the reaction was completed, it was cooled to room temperature, toluene was added, and the pH was adjusted to 7 with hydrochloric acid solution (mass fraction 12%), and the aqueous phase and the organic phase were separated by standing, and the organic phase was taken to remove toluene by vacuum distillation. The temperature was continued to be raised, and the fraction between 190-210°C was collected as intermediate 1;

[0041] S3, in a three-necked flask equipped with a stirring device, add 49.8g of intermediate 1, 30.4g of thiodiethanol, 0.8g of lithium diisopropylamide and 200mL of N,N-dimethylformamide, stir and mix well, pass nitrogen to remove air, heat to 90°C, react for 8h, and after the reaction is completed, remove the solvent by vacuum distillation, and then purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate, the volume ratio of the two is 1:2), and remove the eluent by rotary evaporation to obtain intermediate 2;

[0042] S4, in a three-necked flask equipped with a stirring device, 68.0g of intermediate 2, 43.4g of terephthalic acid and 300mL of N,N-dimethylformamide were mixed and stirred evenly, and then 0.6g of dibutyltin oxide and 41.2g of dicyclohexylcarbodiimide were added, and the reaction temperature was controlled to 85°C, and the reaction was kept warm for 8h. Stirring was continued during the reaction. After the reaction was completed, the reaction was filtered, and part of the solvent was removed by rotary evaporation. Then, it was purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 2:3), and the eluent was removed by rotary evaporation to obtain intermediate 3;

[0043] S5. Ultrasonic disperse 2 g of pre-modified glass fiber in 200 mL of N,N-dimethylformamide for 30 min, add 16.2 g of intermediate 3 and 14.8 g of dicyclohexylcarbodiimide and mix well. Stir and react for 8 h in a water bath at 55 °C. After the reaction is completed, stop heating. After the temperature drops to room temperature, filter and take the filter residue. Wash it three times with anhydrous ethanol and dry it to obtain modified glass fiber.

[0044] Embodiment 3

[0045] 60g of polyphenylene sulfide resin, 15g of polytetrafluoroethylene and 7g of the modified glass fiber prepared in Example 1 were dried in an oven at 80°C, added to a high-speed mixer and mixed with 3g of paraffin wax. After mixing, the mixture was added to a twin-screw extruder for melt spinning to obtain a composite fiber filter material.

[0046] Embodiment 4

[0047] 70g of polyphenylene sulfide resin, 20g of polytetrafluoroethylene and 14g of the modified glass fiber obtained in Example 2 were dried in an oven at 90°C, added to a high-speed mixer and mixed with 5g of epoxy soybean oil. After mixing, the mixture was added to a twin-screw extruder for melt spinning to obtain a composite fiber filter material.

[0048] Embodiment 5

[0049] 80g of polyphenylene sulfide resin, 25g of polytetrafluoroethylene and 21g of the modified glass fiber obtained in Example 2 were dried in an oven at 100°C, added to a high-speed mixer and mixed with 7g of epoxy soybean oil. After mixing, the mixture was added to a twin-screw extruder for melt spinning to obtain a composite fiber filter material.

[0050] Comparative Example 1

[0051] Ordinary glass fibers of the same quality were used to replace the modified glass fibers in Example 5, and the remaining steps were the same as those in Example 5 to obtain a filter material.

[0052] Comparative Example 2

[0053] A commercially available polyphenylene sulfide fiber filter material was used.

[0054] Embodiments 3, 4, 5, and comparative examples 1 and 2 were made into corresponding shapes to be tested according to different test standards, and the following performance tests were performed:

[0055] The national standard GB / T 14337-2008 "Test method for tensile properties of chemical staple fibers" was used to measure the breaking strength and breaking elongation;

[0056] The sample was placed in a xenon lamp aging test chamber for accelerated aging for 14 days. The aging conditions were air atmosphere, xenon lamp wavelength 280-800nm, and irradiation intensity 550W / m 2 , test the breaking strength of the sample after aging (GB / T 14337-2008), and calculate the change in breaking strength; breaking strength retention rate = breaking strength after test / breaking strength before test × 100%;

[0057] Determine the breaking strength of the sample after alkali treatment and acid treatment (GB / T 14337-2008), and calculate the breaking strength retention rate;

[0058] Alkali treatment: sodium hydroxide solution with a pH value of 13 in a 55°C water bath for 4 hours;

[0059] Acid treatment: hydrochloric acid solution with a pH value of 2 in a water bath at 55°C for 4 hours;

[0060] After placing the sample in a constant temperature supply box at 190°C for 24 hours, the thermal shrinkage rate was measured using the YG369S single fiber thermal shrinkage rate tester;

[0061] Determine the flame retardancy of the samples according to UL-94 standard;

[0062] The measurement results are shown in the following table:

[0063]

[0064] It can be seen from the above table that the filter material prepared in the embodiment of the present invention has higher mechanical properties, heat resistance, flame retardancy and oxidation resistance than the control example, and has excellent corrosion resistance, and has important application value in the field of filter material technology.

[0065] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0066] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A composite fiber filter material, characterized in that: Prepared by the following steps: After drying, polyphenylene sulfide resin, polytetrafluoroethylene and modified glass fiber are added into a high-speed mixer with a lubricant for mixing. After mixing, they are added into a twin-screw extruder for melt spinning to obtain a composite fiber filter material.

2. A composite fiber filter material according to claim 1, characterized in that: The modified glass fiber is prepared by the following steps: S1. Soak the chopped glass fiber in acetone for 12 hours, wash, dry, add to ethanol aqueous solution, then add silane coupling agent KH-550, react at 85°C for 5 hours, stir continuously during the reaction, filter, wash, dry, and obtain pre-modified glass fiber; S2, 2-methyl-6-tert-butylphenol and potassium hydroxide were mixed, nitrogen was introduced into the device, and the reaction was carried out at 50°C for 2 hours under nitrogen protection, and methyl acrylate was added dropwise. After the addition was completed, the temperature was raised to 140°C, and the reaction was refluxed for 4 hours. After the reaction was completed, the mixture was cooled to room temperature, toluene was added, and the pH was adjusted to 7. The mixture was allowed to stand to separate the aqueous phase and the organic phase, and the organic phase was distilled under reduced pressure, and the temperature was continued to be raised. The fraction between 190-210°C was collected, which was the intermediate 1; S3, after mixing intermediate 1, dithiodiethanol, lithium diisopropylamide and N,N-dimethylformamide, nitrogen was passed through to remove all air, the temperature was raised to 90°C, and the reaction was carried out for 8 hours. After the reaction was completed, vacuum distillation was performed, column chromatography was performed for purification, and rotary evaporation was performed to obtain intermediate 2; S4, mixing intermediate 2, terephthalic acid and N,N-dimethylformamide, and stirring evenly, then adding dibutyltin oxide and dicyclohexylcarbodiimide, and reacting at 85°C for 8 hours, stirring continuously during the reaction, filtering, rotary evaporation, column chromatography purification, and rotary evaporation to obtain intermediate 3; S5. Ultrasonic disperse the pre-modified glass fiber in N,N-dimethylformamide for 30 minutes, add intermediate 3 and dicyclohexylcarbodiimide, mix and stir evenly, stir and react in a water bath at 55°C for 8 hours, stop heating after the reaction is completed, wait until the temperature drops to room temperature, filter, take the filter residue, wash and dry to obtain modified glass fiber.

3. A composite fiber filter material according to claim 2, characterized in that: In step S1, the ratio of glass fiber, acetone, ethanol aqueous solution, and silane coupling agent KH-550 is 1 g: 100 mL: 100 mL: 7.2 g.

4. A composite fiber filter material according to claim 2, characterized in that: In step S2, the ratio of 2-methyl-6-tert-butylphenol, potassium hydroxide and methyl acrylate is 16.4 g:0.5 g:9.5 g.

5. The composite fiber filter material according to claim 2, characterized in that: In step S3, the ratio of the amount of intermediate 1, thiodiethanol, lithium diisopropylamide, and N,N-dimethylformamide is 24.9 g:15.2 g:0.4 g:100 mL.

6. The composite fiber filter material according to claim 2, characterized in that: In step S4, the ratio of the amount of intermediate 2, terephthalic acid, N,N-dimethylformamide, dibutyltin oxide, and dicyclohexylcarbodiimide is 34.0 g: 21.7 g: 150 mL: 0.3 g: 20.6 g;.

7. The composite fiber filter material according to claim 2, characterized in that: In step S5, the ratio of the amount of pre-modified glass fiber, N,N-dimethylformamide, intermediate 3, and dicyclohexylcarbodiimide is 1 g:100 mL:8.1 g:7.4 g.

8. The composite fiber filter material according to claim 1, characterized in that: The raw materials are calculated in parts by weight as follows: 60-80 parts of polyphenylene sulfide resin, 15-25 parts of polytetrafluoroethylene, 7-21 parts of modified glass fiber, and 3-7 parts of lubricant.